Identification of cardiac wall motion abnormalities in diverse populations by deep learning of the electrocardiogram - Albert J. Rogers; Neal K. Bhatia; Sabyasachi Bandyopadhyay; James Tooley; Rayan Ansari; Vyom Thakkar; Justin Xu; Jessica Torres Soto; Jagteshwar S. Tung; Mahmood I. Alhusseini; Paul Clopton; Reza Sameni; et al. (npj Digital Medicine)
Abstract Cardiac wall motion abnormalities (WMA) are strong predictors of mortality, but current screening methods using Q waves from electrocardiograms (ECGs) have limited accuracy and vary across racial and ethnic groups. This study aimed to identify novel ECG features using deep learning to enhance WMA detection, referencing echocardiography as the gold standard. We collected ECG and echocardiogram data from 35,210 patients in California and labeled WMA using unstructured language parsing of echocardiographic reports. A deep neural network (ECG-WMA-Net) was trained and outperformed both expert ECG interpretation and Q-wave indices, achieving an AUROC of 0.781 (CI: 0.762–0.799). The model was externally validated in a diverse cohort from Georgia (n = 2338), with an AUC of 0.723 (CI: 0.685–0.757). Explainability analysis revealed significant contributions from QRS and T-wave regions. This deep learning approach improves WMA screening accuracy, potentially addressing physiological differences not captured by standard ECG-based methods.